2021
DOI: 10.1093/sysbio/syaa103
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics, Origin, and Diversification of Anthozoans (Phylum Cnidaria)

Abstract: Anthozoan cnidarians (corals and sea anemones) include some of the world's most important foundation species, capable of building massive reef complexes that support entire ecosystems. Although previous molecular phylogenetic analyses have revealed widespread homoplasy of the morphological characters traditionally used to define orders and families of anthozoans, analyses using mitochondrial genes or rDNA have failed to resolve many key nodes in the phylogeny. With a fully resolved, time-calibrated phylogeny f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
92
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 83 publications
15
92
1
Order By: Relevance
“…Importantly, the mutant spirocytes also retain the ability to discharge, confirming this mutation is functionally relevant and is, therefore, a bona fide homeotic transformation ( 7 ). This is the first evidence of homeotic control of cell fate in a cnidarian, suggesting that cellular homeosis is an ancient mechanism that contributed to the expansion of biodiversity that emanated from the last common ancestor of cnidarians and bilaterians, over 800MYA ( 35 ). Specifically, our ability to resurrect an ancestral cell type by manipulating a single gene demonstrates how homeosis links developmental flexibility with environmental selection pressures to drive the emergence of novel cell types.…”
Section: Discussionmentioning
confidence: 88%
“…Importantly, the mutant spirocytes also retain the ability to discharge, confirming this mutation is functionally relevant and is, therefore, a bona fide homeotic transformation ( 7 ). This is the first evidence of homeotic control of cell fate in a cnidarian, suggesting that cellular homeosis is an ancient mechanism that contributed to the expansion of biodiversity that emanated from the last common ancestor of cnidarians and bilaterians, over 800MYA ( 35 ). Specifically, our ability to resurrect an ancestral cell type by manipulating a single gene demonstrates how homeosis links developmental flexibility with environmental selection pressures to drive the emergence of novel cell types.…”
Section: Discussionmentioning
confidence: 88%
“…Fernández-Martínez et al 2019 [ 60 ] described unequivocal octocoral sclerites associated with a tabulate coral. Octocorals as a group are monophyletic [ 39 , 61 63 ] and their higher-level molecular phylogeny is relatively well known. Some smaller taxonomic groups may, however, be poly- or paraphyletic, as is in the case of Keratoisidinae [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first molecular data from corallicolid plastid rRNA suggested that they were deep-branching sisters to apicomplexans [ 14 ]. This was an eye-catching possibility, since corals are also an ancient group of animals [ 23 ], and the closest known photosynthetic relatives of apicomplexans ( Chromera and Vitrella ) are also associated with corals [ 24 , 25 ] ( Fig 2 ). Soon after the discovery of plastids in Plasmodium and Toxoplasma , it was proposed that apicomplexan parasitism might have arisen through an intermediate stage of photosymbiosis [ 26 ].…”
Section: An Ancient Group Of Apicomplexans In An Ancient Group Of Animals?mentioning
confidence: 99%